Current Concepts on Antiplatelet Therapy: Focus on the Novel Thienopyridine and Non-Thienopyridine Agents. (7th October 2010) - Testa, L.; Biondi Zoccai, G. G. L.; Valgimigli, M.; Latini, R. A.; Pizzocri, S.; Lanotte, S.; Laudisa, M. L.; Brambilla, N.; Ward, M. R.; Figtree, G. A.; Bedogni, F.; Bhindi, R.
Abstract : Thienopyridines are a class of drug targeting the platelet adenosine diphosphate (ADP) 2 receptor. They significantly reduce platelet activity and are therefore clinically beneficial in settings where platelet activation is a key pathophysiological feature, particularly myocardial infarction. Ticlopidine, the first of the class introduced to clinical practice, was soon challenged and almost completely replaced by clopidogrel for its better tolerability. More recently, prasugrel and ticagrelor have been shown to provide a more powerful antiplatelet action compared to clopidogrel but at a cost of higher risk of bleeding complications. Cangrelor, a molecule very similar to ticagrelor, is currently being evaluated against clopidogrel. Considering the key balance of ischemic protection and bleeding risk, this paper discusses the background to the development of prasugrel, ticagrelor, and cangrelor and aims to characterise their risk-benefit profile and possible implementation in daily practice.